DAMPAK INDONESIA-AUSTRALIA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IA-CEPA) TERHADAP EKSPOR TEKSTIL DAN PRODUK TEKSTIL REPUBLIK INDONESIA KE AUSTRALIA TAHUN 2019-2023 - Ardi, Andre; Arsalan, Aisha Amanda Putri (Moestopo Journal of International Relations (MJIR), 2024)
The purpose of this research is to find out how the impact of Indonesia and Australia's cooperation in the Indonesia- Australia Comprehensive Economic Partnership Agreement (IA-CEPA) which has officially entered into force on July 5, 2020. The method used in this research is explanatory qualitative method with literature study data collection from various sources such as books, journals, articles, websites and other materials to describe and analyze the impact of the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) on textile and textile product exports. The theories or concepts used in this research include international trade, CEPA, textile and textile products, as well as using the theory of the impact of free trade agreements. The results explain that the impact of the IA-CEPA agreement is the removal of trade barriers, the creation of trade creation in the textile sector, and the creation of trade diversion that shifts imports to several non-FTA country textile products in Australia.